INCIDENCE OF DENTO-PERIODONTAL PATHOLOGY IN GERIATRIC PATIENTS - Mihaela Monica Scutariu; Corina Ciupilan; Mihaela Salceanu; Anca Melian; Doriana Agop Forna; Ioana Sioustis; Oana Ciurcanu (Romanian Journal of Oral Rehabilitation, 2018)
In the context of increasing life expectancy and hence the aging demographic, dentists are increasingly put in the situation of diagnosis and treatment of geriatric patients. Aim of the study is to determine the frequency and type of dento-periodontal lesions in geriatric patients. Material and methods: consist of the clinical examination of a group of 50 patients aged between 55 and 85 years. The results of the research show that a large number of elderly patients exhibit dento-periodontal disease and their diagnosis and treatment is a challenge of the contemporary era. Conclusions: Changes in dental structures are factors that increase the frequency and intensity of carious processes in these patients. Caries lesions are less painful, but they evolve much faster